The Role of Chaplains in Maritime Transport - Liviu Razvan Dragomir; Utureanu Simona Luize (Ovidius University Annals: Economic Sciences Series, 2020)
This paper presents a review on the roles of the chaplaincy service, customary met in the Navy. The aim of the research is to understand and explain the institutional duality of chaplains using ethnography and auto-ethnography as research methods for approaching contemporary issues of chaplaincy.